Identifikasi Penerapan Pembelajaran Berbasis Etnosains di PAUD Se-Kecamatan Selaparang, Kota Mataram - Rohana Oktaviana; Muhammad Tahir; Filsa Era Sativa (Mataram University, 2026)
Ethnoscience-based learning is one of the learning approaches that need to be strengthened in early childhood education to instill cultural values while strengthening children's identity amidst the development of the times. This study aims to identify the application of ethnoscience-based learning in PAUD throughout Selaparang District, Mataram City. So that the forms of application of ethnoscience-based learning can be known. The type of research used is survey research with descriptive quantitative methods. The research subjects were 35 PAUD principals throughout Selaparang District. Data collection methods used include questionnaires, interviews and documentation. Data analysis uses the percentage formula according to Arikunto. The results of the study indicate that the application of ethnoscience-based learning in PAUD throughout Selaparang District is generally in the good category. The use of local materials in learning obtained a percentage of 75.69%, the introduction of local culture was 75.86%, and the use of educational games with local wisdom was 71.90% with a good category. Meanwhile, the integration of local culture-based teaching materials achieved a percentage of 64.29%, and the implementation of exploratory activities in the surrounding environment achieved a percentage of 70.18%, which is in the sufficient category. Therefore, it can be concluded that ethnoscience-based learning has been implemented through various activities such as the use of local materials in learning, the introduction of local culture, the use of educational games with local wisdom, the integration of local culture-based teaching materials, and the implementation of exploratory activities in the surrounding environment. However, improvements are still needed to be more optimal, systematic, and sustainable.